ON THE ISSUE OF CHARACTERISTICS OF THE SUBJECT AND METHOD OF CRIMINAL-LAW REGULATION OF PUBLIC RELATIONS - N. Rybushkin (Russian Journal of Economics and Law)
The article is dedicated to analysis of characteristics of the subject and method of criminal-law regulation. The subject and method of criminal-law regulation are the main categories of criminal law theory. The proper comprehension of the main categories of criminal-law regulation is necessary to solve the problems of criminal legislation as a whole. The author notes the argumentativeness of the problems of the criminal-law theory and makes an attempt to give the answers to some questions, which constitute the subject of the discussion.